Acute mesenteric ischemia with abdominal skin mottling - Masahiro Yabe; Yuji Nomoto; Hitomi Watanabe (Journal of General and Family Medicine)
Abstract We report a rare case of a 90‐year‐old woman with Stage IV lung cancer awaiting transfer to hospice care who developed sudden abdominal and knee skin mottling. Elevated inflammatory markers on blood tests and emergent computed tomography led to a diagnosis of acute mesenteric ischemia, and the patient passed away 7 h later. Skin mottling indicates decreased blood flow in the gastrointestinal tract and is observed during mesenteric ischemia. Abdominal skin mottling may serve as an important physical finding that is detected early and suggests circulatory failure and intestinal ischemia.